Does altitude of birth influence the performance of national- to elite-level colombian cyclists? - Garzon, M.; Leguizamo, J.; Saldarriaga, F.; Galeano, E.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2022)
Objective: To determine whether the altitude of birth/childhood influences the values in peak power output (PPO) and estimated maximum oxygen uptake (estVO2max) in male Colombian road cyclists of different performance levels. This study also aimed to determine whether cyclists born at high altitudes tend to be more successful.